Groundwater Flooding of Superficial Gravels in an Urbanized Catchment - Jonathan D. Paul; Aneena Ajmi; Doris Bolaji‐Dada; Samuel Bordessoule (Journal of Flood Risk Management, 2025)
ABSTRACT Groundwater behavior in superficial gravel aquifers is globally poorly understood, especially across urban regions where drinking water is sourced from elsewhere. This study focuses on one such region around Staines, SE UK, where local River Terrace Gravels form a thin (< 10 m) superficial aquifer. The objective was to explain the unusually broad and long‐lived distribution of flooding by investigating local groundwater level fluctuations and flow. Over a period in January 2024, a targeted citizen science program was instigated to leverage local knowledge of floodwater, which was determined to match groundwater chemistry. Geophysical surveys (ground‐penetrating radar and seismic refraction) were designed to produce high‐resolution water table maps, validated against well measurements. Flow rates and hydraulic conductivity, K, of the gravels were determined both in the field (via pumping and tracer tests) and laboratory, to obviate any scale effects. K depended nonlinearly on hydraulic gradient, with Darcyan behavior breaking down at low (< 0.03) gradients, in conditions approaching turbulent flow. Large and localized fluctuations in groundwater level, combined with the existence of several fast‐flow pathways, are explained by the strong heterogeneity of the gravels, as well as their sensitivity to the imposition of subsurface obstacles such as clay‐lined backfilled gravel pits, or deep basements. These manifestations of urbanization drive observed patterns of groundwater emergence, together with aquifer thickness, rather than changes in river stage or surface elevation alone. Our experience motivates us to suggest that groundwater flooding be considered as significant as fluvial flooding in the production of risk maps by environmental regulatory bodies.